ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR SEMEN YANG TERDAFTAR DI BEI) TAHUN 2015-2018 - Vabiola, Veronica; Panjaitan, Fery; Ruben Manullang, Rizal (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
The thesis paper consists of 84 pages. The purpose of this study is to prove empirically whether company size, profitability, and leverage simultaneously and partially have an influence on CSR disclosure. The population in this study is the cement sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018 totaling 5 companies. The data used is secondary data taken through documentation techniques consisting of the annual report of the cement sector manufacturing companies in 2015-2018. The method of data analysis in this study is multiple regression analysis. The conclusion of the research results based on the results of multiple linear regression analysis and t-test (partial) shows that the size of the company has a positive effect on CSR disclosure. Whereas for profitability and also leverage does not affect CSR disclosure. Based on the f test (simultaneous) shows that company size, profitability, and leverage increase CSR disclosure.